Preliminary evaluation of the proteomic profiling in the hippocampus of aged grazing cattle - Cozzolino, Flora; Canè, Luisa; Sacchettino, Luigi; Gatto, Maria Claudia; Iacobucci, Ilaria; Gatta, Claudia; De Biase, Davide; Di Napoli, Evaristo; Paciello, Orlando; Avallone, Luigi; Monti, Maria; d’Angelo, Danila; et al. (Frontiers in Aging Neuroscience, 2023)
Brain aging is a physiological process associated with physical and cognitive decline; however, in both humans and animals, it can be regarded as a risk factor for neurodegenerative disorders, such as Alzheimer’s disease. Among several brain regions, hippocampus appears to be more susceptible to detrimental effects of aging. Hippocampus belongs to limbic system and is mainly involved in declarative memories and context-dependent spatial-learning, whose integrity is compromised in an age-dependent manner. In the present work, taking advantage of liquid chromatography–tandem mass spectrometry (LC–MS/MS)-based proteomics, we sought to identify proteins differentially expressed in the hippocampus of the aged grazing milk cows. Our exploratory findings showed that, out of 707 identified proteins, 112 were significantly altered in old cattle, when compared to the adult controls, and functional clusterization highlighted their involvement in myelination, synaptic vesicle, metabolism, and calcium-related biological pathways. Overall, our preliminary data pave the way for the future studies, aimed at better characterizing the role of such a subcortical brain region in the age-dependent cognitive decline, as well as identifying early aging markers to improve animal welfare and husbandry practices of dairy cattle from intensive livestock.